(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Survey on the clinical characteristics and impact on quality of life of rosacea patients examined at the National Hospital of Dermatology and Venereology from September 2024 to August 2025. Subjects and Methods: A cross-sectional descriptive study on 122 patients diagnosed with rosacea who presented for examination and treatment at the National Hospital of Dermatology and Venereology from September 2024 to August 2025. Results: Of the 122 patients surveyed, the highest age of disease onset was 40–49 years (27.9%), followed by 30–39 years (24.6%), with a mean age of onset of 43.49 years. The male-to-female ratio was 58.8% to 49.2% (p = 0.856). The disease was affected by the season (79.5%), and was most severe in the summer (46.7%). Common factors influencing the condition included: sun exposure (55.7%), hot weather (52.5%), spicy/hot food (32.8%), and alcohol consumption (30.3%), while 23.7% of patients had no known triggering or aggravating factors. The most common symptoms were persistent erythema (92.6%), flushing/transient erythema (82%), and a burning/stinging sensation (55.7%). The majority of patients experienced a mild impact on their quality of life (47.5%). Conclusion: The study has shown that rosacea can have an onset at various ages, with the highest incidence between 30 and 50, and a nearly equal male-to-female ratio. The condition typically worsens in the summer, but cold, dry winter weather can also affect it. Sun exposure and high temperatures are the most common factors that exacerbate the disease. The most frequent symptoms are persistent erythema, flushing/transient erythema, and a burning or stinging sensation. The disease also causes psychological issues and affects quality of life, though for most patients, the impact is mild.